Pelatihan Membuat Toko Online Menggunakan Aplikasi Marketplace Pada Fatayat NU Ciledug - Nisa , Khoirun; Aulianita, Rizki; Mukhayaroh, Anna; Rakhmah, Syifa Nur; Musyaffa, Nu’man (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
Fathayat Nahdatul Ulama (NU) Ciledug branch is one of the major Islamic organizations in Indonesia under the auspices of Nahdatul Ulama (NU). Most of the members and administrators of this organization are women from the age of 20 to 45 years. The problem with this organization is that some of the board members have trading businesses that are only known by the surrounding environment. By providing E-commerce training, this can be used as a promotional medium by utilizing (Pandemi Akselerasi Perubahan Perilaku Belanja Online)an existing marketplace. Fathayat Nahdatul Ulama (NU) Ciledug is an organization that actively organizes social activities. This is also the reason for the need to hold training on the use of marketplace applications to increase sales so that part of the sales profits can be donated to the social activities carried out.